2011
DOI: 10.5194/angeo-29-945-2011
|View full text |Cite
|
Sign up to set email alerts
|

Statistical evidence for O<sup>+</sup> energization and outflow caused by wave-particle interaction in the high altitude cusp and mantle

Abstract: Abstract. We present a statistical study of the low (<1 Hz) frequency electric and magnetic field spectral densities observed by Cluster spacecraft in the high altitude cusp and mantle region. At the O + gyrofrequency (0.02-0.5 Hz) for this region the electric field spectral density is on average 0.2-2.2 (mV m −1 ) 2 Hz −1 , implying that resonant heating at the gyrofrequency can be intense enough to explain the observed O + energies of 20-1400 eV. The relation between the electric and magnetic field spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(78 citation statements)
references
References 32 publications
7
71
0
Order By: Relevance
“…The largest differences from the new ionization (cometary) case are as follows: (a) the massloading regions are geomagnetically connected to the ionosphere through which separated charges can flow, and (b) the mass-loading ions are already heated with non-zero gyrating velocity when they are supplied from one boundary along the magnetic field perpendicular (in the z direction) to the inflow. In Cluster observations at the Earth, these mass-loading ions coming from the ionosphere have thermal velocities of > 100 km s −1 in Nilsson et al (2006) and Waara et al (2011). This value is comparable to the decelerated solar wind speed (about 100 km s −1 in the plasma mantle) as shown in Fig O + stream line in the plasma mantle (as defined in are plotted.…”
Section: Amount Of Converted Kinetic Energy By the Escaping O +supporting
confidence: 49%
“…The largest differences from the new ionization (cometary) case are as follows: (a) the massloading regions are geomagnetically connected to the ionosphere through which separated charges can flow, and (b) the mass-loading ions are already heated with non-zero gyrating velocity when they are supplied from one boundary along the magnetic field perpendicular (in the z direction) to the inflow. In Cluster observations at the Earth, these mass-loading ions coming from the ionosphere have thermal velocities of > 100 km s −1 in Nilsson et al (2006) and Waara et al (2011). This value is comparable to the decelerated solar wind speed (about 100 km s −1 in the plasma mantle) as shown in Fig O + stream line in the plasma mantle (as defined in are plotted.…”
Section: Amount Of Converted Kinetic Energy By the Escaping O +supporting
confidence: 49%
“…The DC-level (0 Hz) in the data is removed by subtracting the mean of each time window for the EFW. The wave data set is described in more detail by Waara et al (2011). In that study, it was shown that the electric field to magnetic field spectral density ratio (E/B ratio) of the observed waves agreed with the Alfvén wave velocity as calculated from the background magnetic field and ion density estimates obtained using ion spectrometer data.…”
Section: Instrumentation and Datamentioning
confidence: 62%
“…The study of Waara et al (2010) was followed up with a statistical study of the electric and magnetic field spectral densities in the frequency range below 1 Hz, in the general vicinity of the high altitude oxygen gyrofrequency . In Waara et al (2011), it was shown that, statistically, the gyroresonance model could, in fact, reproduce the observed average perpendicular temperature and average parallel velocity for altitudes between 8-15 R E in the cusp/mantle region given the average spectral density. It was assumed that 50 % of the observed wave activity at the local O + gyrofrequency was due to left-hand polarized waves, which can effectively heat the ions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations